Growth, Development and Yield Indicators of Triticale Varieties in the Conditions of Karakalpakstan - Quanyshbaevich, Turgunbayev Aydarbek; Dauletbay, Edenbayev; Qahramanovich, Azizov Qobuljon; Bozarovich, Khudayqulov Jonibek; o‘g‘li, Bozorbayev Sherzod Saparbek (American Journal of Botany and Bioengineering, 2025)
Triticale (/trɪtɪˈkeɪliː/; ×Triticosecale) is a hybrid of wheat (Triticum) and rye (Secale) first bred in laboratories during the late 19th century in Scotland and Germany.[8] Commercially available triticale is almost always a second-generation hybrid, i.e., a cross between two kinds of primary (first-cross) triticale. As a rule, triticale combines the yield potential and grain quality of wheat with the disease and environmental tolerance (including soil conditions) of rye. In this article describes the biological and morphological characteristics of triticale (Triticosecale) samples grown on grassland and saline soils in the Republic of Karakalpakstan, their growing season, yield, and laboratory test results. According to the results of the study, the varieties "Sergey" and "Tikhon" were distinguished by high yield, good grain quality, and adaptability to climatic conditions.